2022
DOI: 10.1186/s12890-022-02126-4
|View full text |Cite
|
Sign up to set email alerts
|

A feasibility randomised trial comparing therapeutic thoracentesis to chest tube insertion for the management of pleural infection: results from the ACTion trial

Abstract: Background Pleural infection is a complex condition with a considerable healthcare burden. The average hospital stay for pleural infection is 14 days. Current standard of care defaults to chest tube insertion and intravenous antibiotics. There have been no randomised trials on the use of therapeutic thoracentesis (TT) for pleural fluid drainage in pleural infection. Aims and objectives To assess the feasibility of a full-scale trial of chest tube v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Nonetheless, although most eligible patients agreed to be randomly allocated to surgery, and that anesthesia risk precluded only a minority of participants from this allocation, a minimum fitness criterion may potentially optimize compliance in a future phase III study while maintaining the strength of MIST-3 in avoiding the selection bias of previous surgical RCTs ( 13 , 14 ), and the latter patients in their seventh and eighth decades of life were successfully treated surgically. With increasing experience, expertise, and safety demonstrated with VATS as a treatment modality, we strongly advocate that such patients are included in future trials given their increasing representation in pleural infection cohorts ( 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, although most eligible patients agreed to be randomly allocated to surgery, and that anesthesia risk precluded only a minority of participants from this allocation, a minimum fitness criterion may potentially optimize compliance in a future phase III study while maintaining the strength of MIST-3 in avoiding the selection bias of previous surgical RCTs ( 13 , 14 ), and the latter patients in their seventh and eighth decades of life were successfully treated surgically. With increasing experience, expertise, and safety demonstrated with VATS as a treatment modality, we strongly advocate that such patients are included in future trials given their increasing representation in pleural infection cohorts ( 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…86 The Aspiration versus Chest Tube (ACTion) trial demonstrated the feasibility of TT in 10 patients with complicated parapneumonic effusion without significant loculations. 87 This approach will need evaluation in larger studies.…”
Section: Nonsurgical Management Of Parapneumonic Effusion Fitzgerald ...mentioning
confidence: 99%
“…The ACTion trial (Aspiration versus Chest Tube drainage for pleural infectION), which is a feasibility study that randomised 10 patients with pleural infection to TT or chest tube insertion, with five patients in each arm, showed that the TT arm had a significantly shorter overall mean± sd hospital stay (5.4±5.1 days) compared to the chest tube control group (13±6.0 days; p=0.04) [ 57 ]. There was no difference in the total number of pleural procedures required per patient among both groups.…”
Section: Management Of Pleural Infectionmentioning
confidence: 99%